2012
DOI: 10.1002/nbm.1804
|View full text |Cite
|
Sign up to set email alerts
|

Improved MR‐based characterization of engineered cartilage using multiexponential T2 relaxation and multivariate analysis

Abstract: Noninvasive monitoring of tissue quality would be of substantial use in the development of cartilage tissue engineering strategies. Conventional MR parameters provide noninvasive measures of biophysical tissue properties and are sensitive to changes in matrix development, but do not cleanly distinguish between groups with different levels of matrix development. Furthermore, MR outcomes are nonspecific, with specific changes in matrix components resulting in changes in multiple MR parameters. To address these l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 69 publications
1
28
0
Order By: Relevance
“…This is important in order (a) to assess the efficacy of tissue engineering approaches at an early growth stage, (b) for providing an accurate assessment of engineered tissue growth postimplantation, and (c) for monitoring the healing of cartilage after treatment. Magnetic resonance imaging (MRI) is a leading non-invasive characterization technique for monitoring growth in cartilage tissue engineering [2][3][4][5][6][7]. Research Cartilage tissue in its native state contains chondrocytes (~1%) imbedded in an extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…This is important in order (a) to assess the efficacy of tissue engineering approaches at an early growth stage, (b) for providing an accurate assessment of engineered tissue growth postimplantation, and (c) for monitoring the healing of cartilage after treatment. Magnetic resonance imaging (MRI) is a leading non-invasive characterization technique for monitoring growth in cartilage tissue engineering [2][3][4][5][6][7]. Research Cartilage tissue in its native state contains chondrocytes (~1%) imbedded in an extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…Reprinted with permission from Lin et al 112 The SVM approach has been extended to classification of maturation stage in engineered cartilage grown from bovine chondrocytes using a PGA scaffold. 111 The best univariate classifier for maturation, k m , showed a validation set classification accuracy of 0.85. In contrast, the best bivariate classifier in these engineered cartilage constructs was (k m , ADC), with an accuracy of 0.98.…”
Section: Multivariate Machine Learning Analysis Of Mri Parametersmentioning
confidence: 99%
“…110 Similar findings were obtained in the univariate analysis of engineered cartilage. 111 A number of multivariate approaches have been applied to MRI indices of cartilage matrix in an effort to define tissue status with greater sensitivity and specificity. 112,113 Similar to multiexponential T 2 analysis, this approach was initially applied to normal and enzymatically degraded cartilage.…”
Section: Multivariate Machine Learning Analysis Of Mri Parametersmentioning
confidence: 99%
“…It is likely that during engineered tissue growth, both the T 1 and T 2 relaxation times would decrease due to accumulation of both proteoglycans and collagen. It is possible to separate the contributions of water, proteoglycans and collagen content to the observed T 2 data of engineered cartilage using multiexponential analysis, 38,39,94 but such experiments require a very high SNR, hence, use of signals from the entire sample, not from individual image pixels. Nevertheless, using this technique, Reiter et al have found that the proteoglycan component in cartilage tissue taken from young and mature bovine nasal cartilage was highly correlated with T 2 and with the biochemical analysis.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…MRS and imaging are wellestablished techniques that have been used to probe the structure and dynamics of biochemical changes in engineered tissues. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] MR elastography, while relatively new, is rapidly being employed to assess the mechanical properties of engineered tissues. 30,43 Using MR spectroscopy, imaging, and elastography together, it is possible to create three-dimensional (3D) maps of chemical shifts, relaxation times, diffusion coefficient, spectral couplings, and tissue stiffness.…”
mentioning
confidence: 99%